'A TWILIGHT SMELLING OF VERGIL': E. E. CUMMINGS, CLASSICS, AND THE GREAT WAR*. (October 2014) - Rosenblitt, Alison
<x content-type="archive" xml:space="preserve">Abstract</x> <disp-quote> The opened door showed a room, about sixteen feet short and four feet narrow, with a heap of straw in the further end. My spirits had been steadily recovering from the banality of their examination; and it was with a genuine and never-to-be-forgotten thrill that I remarked, as I crossed what might have been the threshold : 'Mais, on est bien ici.' A hideous crash nipped the last word. I had supposed the whole prison to have been utterly destroyed by earthquake, but it was only my door closing.... </disp-quote>Here, in a passage taken from the novelized version of his own imprisonment in France in 1917, the American modernist poet E. E. Cummings describes the moment of confrontation with the first of his prison cells. He had volunteered for ambulance service in France during the First World War, but his service lasted only a few months before he and his friend William Slater Brown were arrested and incarcerated – wrongfully suspected of espionage – in a brutal French detention camp at La Ferté-Macé.